Software database project : project C - Ong, Jaoon (Nanyang Technological University, 2020)
Network graph analysis is becoming increasingly relevant for many reasons in our society today. One reason is the ability to find a social circle of a person and track down the person through his contacts. This will be helpful for NTU School of EEE to stay accountable for the well-being of their students. This paper runs through the development of the network graph along with a web application that visualizes the network. To develop and display the network graph, an adjacency matrix was used as the primary data structure for the graph data. The adjacency matrix was coded in Python and visualized on the web application coded in React. The network visualization also implements an interactive graph module to allow intuitive use by the user. This paper concludes with suggestions on future research and implementation ideas.